(3ebGdI aj JRjja ebOeGJ CHj Sgd GdbhUi aj Cf fSHI GdbWQ Edi fSHI GdhGMO Edi KdGKI hJSYs - (3fLe GdOjf CHh GdaJhM CMeO Hf eMeO Hf GdSQj hcGf jYQa HGHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3bO cfJ CSeY bOjekG HeOjfI GdSde Cf dCHi Sgd GdbhUi ebGdI ai Cf fSH GdbWQ Edi GdeMjW fSHI GdhGMO Edi KdGKI hJSY hCJYLH EPG cGfJ gPg GdebGdI JHWd eG PcQg CQTejOS s
(3BNQgG (B:s
(3abO HGf Cf eQcR GdbWGYjf dGjecf Cf jchf hGMOkG hPdc eG CQOfG Cf fHjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs